More than meets the eye: Predator‐induced pupil size plasticity in a teleost fish. Issue 10 (16th August 2020) - Vinterstare, Jerker; Hulthén, Kaj; Nilsson, Dan E.; Nilsson, Per Anders; Brönmark, Christer
Abstract: Most animals are visually oriented, and their eyes provide their 'window to the world'. Eye size correlates positively with visual performance, because larger eyes can house larger pupils that increase photon catch and contrast discrimination, particularly under dim light, which have positive effects on behaviours that enhance fitness, including predator avoidance and foraging. Recent studies have linked predation risk to selection for larger eyes and pupils, and such changes should be of importance for the majority of teleost fishes as they have a pupil that is fixed in size (eyes lack a pupillary sphincter muscle) and, hence, do not respond to changes in light conditions. Here, we quantify eye and pupil size of individual crucian carp, a common freshwater fish, following controlled manipulations of perceived predation risk (presence/absence). We also tested if crucian carp responded to increased predation risk by shifts in diel activity patterns. We found that crucian carp show phenotypic plasticity with regards to pupil size, but not eye size, as pupil size increased when exposed to predators (pike). Predator‐exposed crucian carp also shifted from diurnal to nocturnal activity. Using a modelling exercise, we moreover show that the plastically enlarged pupils significantly increase visual range, especially for small objects under dim light conditions. Overall, our results provide compelling evidence for predator‐induced pupil enlargement resulting in enhanced visual capabilities in a teleost fish. Pupil size plasticity in combination with the observed shift towards nocturnal activity may allow for efficient foraging also under dark conditions when predation risk from diurnal and visually oriented predators is reduced. The data highlight the powerful role of predation risk for eye development and evolution. Abstract : The authors examine predator‐induced plasticity in eye morphology of a teleost fish and show that perceived predation risk increases the size of the pupil. Further, the authors show that these changes in pupil size are adaptive when shifting from a diurnal to a nocturnal lifestyle, as demonstrated when coexisting with natural predators.